STUDI KASUS PESERTA DIDIK YANG BERTINGKAH LAKU AGRESIF DI SALAH SATU SEKOLAH SMA - Tiarma Fitri Malau; Yesika Lumiam Sinaga; Rut Lumayan Silitonga; Sartika Afrida Padang; Hartati Sepriani Gultom; Maria Widiastuti (Pusat Riset dan Inovasi Nasional, 2023)
Aggressive behavior is dangerous when it causes intentional physical or psychological harm to another person. Adolescents who successfully complete developmental activities will be in a favorable state of social adjustment for the rest of their lives. However, if youth fail in the growth process, they run the risk of committing crimes and becoming more arbitrary in their power over others. Children engage in ways that often result in aggressive behavior, both individually and collectively. Fighting, forming convoys on the street to block traffic, skipping classes, and using unpleasant language such as swearing, insults, and ridicule are examples of aggressive behavior that are common among students. The research method uses a qualitative approach with case studies. The results of this study are discussed. is that there are students who have aggressive behavior, namely Physical Aggressive and Verbal Aggressive and are factored from External and Internal factors, then a form of handling can be carried out by researchers.